Hilangnya Peran Orang Tua Terhadap Kondisi Psikologis dan Mental Anak "Studi Kasus: Emerging Adulthood" - Radhiah Amna (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The role of parents in a child's psychological and mental development is very important. However, in some cases, this role may be lost or reduced, which will have an impact on the child's psychological and mental state. In this context, the loss of parental roles may occur for various reasons, such as divorce, death, economic or other conditions that result in parents being unable to fulfill their roles fully. In many cases, this leads to children feeling deprived of attention, protection and affection from their parents. This study focuses on "Emerging Adulthood", the transition phase from adolescence to adulthood, where individuals undergo major changes in various aspects of their lives. This study aims to understand the impact of the loss of parental role in this phase to provide in-depth insights based on individual experiences.